FAKTOR RISIKO TERJADINYA PREEKLAMPSIA DI RSUD SYEKH YUSUF GOWA - Suriani Tahir; Ny. Daswati (Voice of Midwifery, 2017)
Preeclampsia and eclampsia are a collection of symptoms that occur in pregnant women, maternity and in the puerperium consisting of triad proteinuri, hypertension, and edema, sometimes accompanied by convulsions to coma. The mother showed no signs of previous vascular or hypertensive disorders The aim of this research is to know the correlation between risk factor to preeclampsia event.The type of research used is descriptive analytic research with cross sectional study approach. This research was conducted in RSUD Syekh Yusuf Gowa Year 2014-2015, research time June 2016 until May 2017, sample in this research is all pregnant women who have preeclampsia and recorded in status of mother in medical record Syech Yusuf Gowa Hospital Year 2014-2015. Sampling technique is simple random sampling and analysis used is univariate and bivariate analysis.Conclusion: There is no significant relationship between maternal age and DM disease with risk of preeclampsia. There is a significant relationship between gravidity, gestational age, type of preeclampsia pregnancy. Keywords :  Preeclampsia, Hypertension, Pregnant Mother